Система мониторинга артиллерийских боеприпасов и анализ ее возможных структур по степени рациональности - Анипко, О. Б.; Хайков, В. Л. (НТУ "ХПИ", 2013)
Для сучасного стану запасів артилерійських пострілів обгрунтована необхідність переходу до системи їх моніторингу. Наведено аналіз структур моніторингу за ступенем їх раціональності.

For current state of artillery ammunition stocks necessity of transition to monitor their condition is proved. The analysis of the monitoring system structures ofaccording to their rationality is performed.
Artillery ammunition monitoring system and analysis of its possible structures on the degree of rationality
Keywords: аналитический модуль; минимизация финансовых затрат; снаряд; модель трансформации характеристик; РКТП